Some Kinematical Variables and Their Relationship with Position Two Blocking Accuracy by Pivot Volleyball Club Players in the Primer League - Sattar, Hasnaa; Issa, Al-hamza (Journal of Physical Education, 2018)
The research aimed at identifying the relationship between some kinematical variables and the accuracy of position two blocking performed by pivot volleyball players in the premier league 2016 – 2017. The researchers used the deceptive method. The subjects were pivot volleyball players from the top six clubs. The kinematical variables were selected using videography. The results showed weakness in position two blocking accuracy. Finally they recommended that pivot volleyball players should increase the approaching steps speed to gain vertical speed. Keywords: kinematical variables, blocking, volleyball.